LATIHAN PROGRESSIVE MUSCLE RELAXATION (PMR) TERHADAP PENURUNAN FATIGUE PADA PASIEN PENYAKIT GINJAL KRONIK DI UNIT HEMODIALISA RSUD DR. M. HAULUSSY AMBON - Feby Adolf Metekohy (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2021)
Background: Chronic kidney disease patients undergoing hemodialysis will experience fatigue. The prevalence of chronic kidney disease (CKD) in 2017 worldwide was 10-15% and undergoing hemodialysis was 64.9%. In Indonesia, CKD continues to increase, in 2018 the prevalence was 3.8% and 85% underwent hemodialysis. The role of nurses is very important in overcoming fatigue, starting with a careful assessment of the level of fatigue so that appropriate interventions can be given to reduce fatigue. One of the interventions that can be done is to provide progressive muscle relaxation (PMR) exercises. PMR is a technique specifically designed to help relieve muscle tension that occurs when conscious. Objective: This study aims to determine the effect of PMR exercise on reducing fatigue in RSUD dr. M. Haulussy Ambon. Method: The research design used a pre-experimental design with a One group pre post test design approach. The sampling technique used purposive sampling technique with a sample size of 30 patients. Data analysis using Paired sample t-test. Result: The results showed that before PMR exercise 63.3% experienced fatigue with a mean value of 26.87 and after PMR exercise 46.7% experienced fatigue with an average value of 23.20. Statistical test results show p value = 0.004 (< 0.05). Conclusion: there is a significant effect between PMR exercise on reducing fatigue in patients with chronic kidney failure at dr. M. Haulussy Ambon.